The Effect of Service Quality and User Value on the Satisfaction and Loyalty of Users at Library and Archives of Padang City - Hayati, Sefni; Heryanto, (Technium Social Sciences Journal, 2020)
This study aims to determine and analyze the effect of service quality and user value on the satisfaction and loyalty of users at the Padang City Library and Archives Service. The sample used was 100 respondents. The sampling technique is purposive sampling. The data is processed using SPSS 16. The type of data used is primary data by distributing questionnaires. Data analysis method with path analysis technique. The results of the study found that the quality of service had a significant effect on the loyalty of users at the Padang City Library and Archives Service, the value of users had a significant effect on the loyalty of users at the City of Library and Archives Service, the quality of service had a significant effect on the satisfaction of visitors at the Department of Library and Archives of Padang, the value of users have a significant effect on the satisfaction of library users in the Padang City Library and Archives Office, satisfaction has a significant effect on the loyalty of users in the Library and City Archives Office in Padang, the quality of service through satisfaction has no effect on loyalty and so does the value of users through satisfaction does not affect the loyalty of users in the Padang City Library and Archives Service.